Inhibition of Return Decreases Early Audiovisual Integration: An Event-Related Potential Study - Peng, Xing; Tang, Xiaoyu; Jiang, Hao; Wang, Aijun; Zhang, Ming; Chang, Ruosong (Frontiers in Human Neuroscience, 2021)
Previous behavioral studies have found that inhibition of return decreases the audiovisual integration, while the underlying neural mechanisms are unknown. The current work utilized the high temporal resolution of event-related potentials (ERPs) to investigate how audiovisual integration would be modulated by inhibition of return. We employed the cue-target paradigm and manipulated the target modality and cue validity. Participants were required to perform the task of detection of visual (V), auditory (A), or audiovisual (AV) targets shown in the identical (valid cue) or oppossed (invalid cue) side to be the preceding exogenous cue. The neural activities between AV targets and the sum of the A and V targets were compared, and their differences were calculated to present the audiovisual integration effect in different cue validity conditions (valid, invalid). The ERPs results showed that a significant super-additive audiovisual integration effect was observed on the P70 (60~90 ms, frontal-central) only under the invalid cue condition. The significant audiovisual integration effects were observed on the N1 or P2 components (N1, 120~180 ms, frontal-central-parietal; P2, 200~260 ms, frontal-central-parietal) in both valid cue as well as invalid cuecondition. And there were no significant differences on the later components between invalid cue andvalid cue. The result offer the first neural demonstration that inhibition of return modulates the early audiovisual integration process.